In Vivo Evaluation of an Injectable Premixed Radiopaque Calcium Phosphate Cement - Jonas Åberg; Eszter Pankotai; Gry Hulsart Billström; Miklós Weszl; Sune Larsson; Csaba Forster-Horváth; Zsombor Lacza; Håkan Engqvist (International Journal of Biomaterials)
In this work a radiopaque premixed calcium phosphate cement (pCPC) has been developed and evaluated in vivo. Radiopacity was obtained by adding 0–40 % zirconia to the cement paste. The effects of zirconia on setting time, strength and radiopacity were evaluated. In the in vivo study a 2 by 3.5 mm cylindrical defect in a rat vertebrae was filled with either the pCPC, PMMA or bone chips. Nano-SPECT CT analysis was used to monitor osteoblast activity during bone regeneration. The study showed that by adding zirconia to the cement the setting time becomes longer and the compressive strength is reduced. All materials evaluated in the in vivo study filled the bone defect and there was a strong osteoblast activity at the injury site. In spite of the osteoblast activity, PMMA blocked bone healing and the bone chips group showed minimal new bone formation. At 12 weeks the pCPC was partially resorbed and replaced by new bone with good bone ingrowth. The radiopaque pCPC may be considered to be used for minimal invasive treatment of vertebral fractures since it has good handling, radiopacity and allows healing of cancellous bone in parallel with the resorption of the cement.